Slide rule maths doubles computer speeds. - Durham, Tony (Times Higher Education Supplement, 1999)
Deals with improved computer arithmetic. Information on a microprocessor which runs programs fast; Use of transformation logarithms in speed-up; Details on floating-point techniques.